CHEMICAL PROFILING OF BUCHANANIA LANZAN SPRENG ESSENTIAL OIL AND ITS BIOLOGICAL ACTIVITIES - S, AJITH; V, KRISHNA; KUMAR S, RAVI; KUMAR NM, VINAY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was designed to evaluate the chemical composition of the essential oil of Buchanania lanzan Spreng extracted from the seeds and to evaluate in vitro antimicrobial antioxidants and molecular docking studies of the major bioactive compounds of essential oil. Methods: The essential oil was obtained by hydrodistillation of the B. lanzan seeds and analyzed by gas chromatography-mass spectrometry (GC-MS). Antibacterial activity was evaluated against Pseudomonas aeruginosa, Salmonella typhi, Vibrio cholerae, Staphylococcus aureus, and Streptococcus pneumoniae clinical isolates by disk diffusion method and resazurin assay determined the minimum inhibitory concentration. The in vitro antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2) scavenging assay; the essential oil major bioactive compounds are Androstan-3-ol, Campesterol, and γ-Sitosterol were docked against bacterial protein DNA gyrase. Results: GC-MS analysis exhibited the presence of 19 bioactive compounds. The essential oil showed that significant antibacterial activity was noticed against V. cholerae and S. typhi with the highest zone of inhibition 15.67–1.20 and 13.83–0.33, respectively. Antioxidant activity in DPPH and H2O2 scavenging assays with IC50 values of 134.23 and 191.24, respectively. The molecular docking of Androstan-3-ol and γ-Sitosterol with bacterial DNA gyrase unveiled a good binding affinity of −6.4 kcal/mol and −6.3 kcal/ mol, respectively. Conclusion: It could be concluded that the essential oils potential sources of antibacterial, antioxidant activities, and molecular docking of bioactive components. The results of this study provide partial scientific support for the traditional application of essential oils to cure diarrhea and also major bioactive compounds responsible for important biological activities.